An IT System for Assessing Noise Level Distribution in Historical Urban Centers - MELNYK, Mykhaylo; KAMISIŃSKI, Tadeusz Marek; KINASZ, Roman; VYNAROVYCH, Roman (Archives of Acoustics, 2025)
This article explores the challenge of identifying noise-generating factors in traffic flows (TFs) within the constrained spaces and imperfect transport networks of historical cities, using Lviv as a case study. Experimental studies were conducted to measure the equivalent noise levels at different times of the day on selected streets in Lviv. These streets are characterized by dense development, paved surfaces, and a high volume of vehicular and rail traffic. The study identified correlations between noise levels, traffic volumes, and vehicle speeds during daytime and nighttime periods. Notably, vehicle speed was found to have a more significant impact on noise levels than the number of vehicles. Through the analysis of these findings, empirical mathematical models were developed and validated using the Lagrange interpolation polynomial to predict noise pollution levels on selected streets at specific times. The developed computer system enables quick forecasting of noise levels for a given street while simultaneously provides data to manage TF as a factor affecting noise generation. Crucially, this tool can also assist in calculating the required specifications for acoustic insulation on building façades adjacent to these TFs.